2001
DOI: 10.2337/diabetes.50.2007.s154
|View full text |Cite
|
Sign up to set email alerts
|

Beta-cell adaptation and decompensation during the progression of diabetes.

Abstract: Inadequate ␤-cell function is an essential component of all forms of diabetes. The most obvious problem is a failure to maintain sufficient ␤-cell mass and function to cope with whatever insulin resistance is present. The most striking functional defect is a loss of acute glucose-induced insulin secretion (GIIS). This review discusses the ways in which ␤-cells successfully adapt to increased demand and then decompensate as diabetes develops. Successful adaptation is achieved through increased ␤-cell mass and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
328
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(346 citation statements)
references
References 45 publications
10
328
0
8
Order By: Relevance
“…Concomitantly, its responsivity to insulin greatly increases during weaning. After weaning, the plasticity and turnover of islets and of beta cells are diminished and this emphasizes the importance of adequate prenatal and early postnatal pancreatic development [33,34]. Both low protein diet and caloric restriction studies in animals have been shown to influence pancreatic development [27].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, its responsivity to insulin greatly increases during weaning. After weaning, the plasticity and turnover of islets and of beta cells are diminished and this emphasizes the importance of adequate prenatal and early postnatal pancreatic development [33,34]. Both low protein diet and caloric restriction studies in animals have been shown to influence pancreatic development [27].…”
Section: Discussionmentioning
confidence: 99%
“…Euglycaemichyperinsulinaemic clamps were performed as previously described [17] in 9-week old, conscious, catheterised mice that had fasted for 16 h. In vivo experiments lasted for 240 min and consisted of a 120-min basal period, directly followed by a 120-min euglycaemic-hyperinsulinaemic clamp. During the basal period a prime-continuous [3] glucose infusion (370 kBq bolus, 3.7 kBq/min) was started and continued to determine rates of whole-body glucose turnover. After the 120-min basal infusion period, a primecontinuous insulin infusion (10 mU kg −1 min −1 ) was started at time 0 min, raising insulin levels to within a physiological range.…”
Section: Methodsmentioning
confidence: 99%
“…Steady-state conditions for plasma glucose concentration and specific activity were achieved within 70 min and a single 2-deoxy-D-[1-14 C]glucose injection was administered at time 75 min. To determine plasma [3] glucose, 3 Histology of adipose tissue Adipose tissue was fixed in 4% buffered formaldehyde, rinsed in phosphate-buffered saline and dehydrated in a graded series of 50-100% ethanol followed by propylene oxide. Tissue was infiltrated with propylene/Epon-812 mixtures by gradually increasing the resin concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of pancreatic beta cells to secrete insulin in response to nutrient stimulation depends on adequate expression of genes important for glycolysis, mitochondrial metabolism and insulin biosynthesis, such as preproinsulin, Glut2 (also known as Slc2a2) and glucokinase, and on the repression of genes potentially deleterious to beta cell function [1], including hexokinase 1 and lactate dehydrogenase A [2]. Besides acutely regulating insulin biosynthesis and secretion, subacute and prolonged changes in nutrient availability exert pleiotropic effects on the beta cell phenotype, such as altered function, survival, growth and differentiation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%